Analysis of Consumer Behavior in Online Shopping During in the Pandemic Covid-19 Period in Bengkalis Sub-District - Suriyani Suriyani; Teguh Widodo (Politeknik Negeri Bengkalis, 2021)
This study aims to determine the factors that influence consumer behavior in online shopping, determine the dominant factors and determine the lowest factor consumer behavior in shopping online during the covid-19 period in Bengkalis district. Method of collecting data is through a survey through a questionnaire instrument. Research questionnaires were presented to respondents through distributing online questionnaires on uploaded internet links, number of samples obtained was 100 respondents in total. The sampling technique used was a non-probability sampling technique, a type of snowball sampling. The results show that personal is the dominant factor while culture is the lowest factor influencing consumer behavior, where both of these factors are included in the high category. respondents who filled out the questionnaire to be able to help pass it on to other potential respondents. It is hoped that in the future this research can continue to be developed in accordance with the times.